From Stock Bottle to Vaccine: Elucidating the Particle Size Distributions of Aluminum Adjuvants Using Dynamic Light Scattering - Shardlow, Emma; Mold, Matthew; Exley, Christopher (Frontiers in Chemistry, 2017)
The physicochemical properties of aluminum salts are key determinants of their resultant adjuvanticity in vivo when administered as part of a vaccine. While there are links between particle size and the efficacy of the immune response, the limited literature directly characterizing the PSD of aluminum adjuvants has stymied the elucidation of such a relationship for these materials. Hence, this comparative study was undertaken to monitor the PSD of aluminum adjuvants throughout the process of vaccine formulation using DLS. A significant proportion of the stock suspensions was highly agglomerated (>9 μm) and Alhydrogel® exhibited the smallest median size (2677 ± 120 nm) in comparison to Adju-Phos® or Imject alum® (7152 ± 308 and 7294 ± 146 nm respectively) despite its large polydispersity index (PDI). Dilution of these materials induced some degree of disaggregation within all samples with Adju-Phos® being the most significantly affected. The presence of BSA caused the median size of Alhydrogel® to increase but these trends were not evident when model vaccines were formulated with either Adju-Phos® or Imject alum®. Nevertheless, Alhydrogel® and Adju-Phos® exhibited comparable median sizes in the presence of this protein (4194 ± 466 and 4850 ± 501 nm respectively) with Imject alum® being considerably smaller (2155 ± 485 nm). These results suggest that the PSD of aluminum adjuvants is greatly influenced by dilution and the degree of protein adsorption experienced within the vaccine itself. The size of the resultant antigen-adjuvant complex may be important for its immunological recognition and subsequent clearance from the injection site.